Nerve guidance conduit with a hybrid structure of a PLGA microfibrous bundle wrapped in a micro/nanostructured membrane - Peng, Shih-Wen; Li, Ching-Wen; Chiu, Ing-Ming; Wang, Gou-Jen (International journal of nanomedicine, 2017)
Nerve repair in tissue engineering involves the precise construction of a scaffold to guide nerve cell regeneration in the desired direction. However, improvements are needed to facilitate the cell migration/growth rate of nerves in the center of a nerve conduit. In this paper, we propose a nerve guidance conduit with a hybrid structure comprising a microfibrous poly(lactic- -glycolic acid) (PLGA) bundle wrapped in a micro/nanostructured PLGA membrane. We applied sequential fabrication processes, including photolithography, nano-electroforming, and polydimethylsiloxane casting to manufacture master molds for the repeated production of the PLGA subelements. After demolding it from the master molds, we rolled the microfibrous membrane into a bundle and then wrapped it in the micro/nanostructured membrane to form a nerve-guiding conduit. We used KT98/F1B-GFP cells to estimate the migration rate and guidance ability of the fabricated nerve conduit and found that both elements increased the migration rate 1.6-fold compared with a flat PLGA membrane. We also found that 90% of the cells in the hybrid nano/microstructured membrane grew in the direction of the designed patterns. After 3 days of culturing, the interior of the nerve conduit was filled with cells, and the microfiber bundle was also surrounded by cells. Our conduit cell culture results also demonstrate that the proposed micro/nanohybrid and microfibrous structures can retain their shapes. The proposed hybrid-structured conduit demonstrates a high capability for guiding nerve cells and promoting cell migration, and, as such, is feasible for use in clinical applications.